The Ambivalent Role of Religion for Sustainable Development: A Review of the Empirical Evidence - Matthias Basedau; Simone Gobien; Sebastian Prediger (German Institute of Global and Area Studies (GIGA), 2017)
Until recently, academia has largely neglected the impact of religion on sustainable development. However, empirical studies have shown that religion remains important in many societies and that its importance has been increasing since the beginning of the new millennium. This paper reviews the empirical quantitative literature on the effect of religion on development from the last decade. We start by disaggregating the concepts of religion and sustainable development into four religious and three developmental dimensions and proposing a framework to identify causal mechanisms. Numerous mechanisms are possible, and this complexity explains why only a few uncontested findings exist. Religion is ambivalent vis-à-vis development: although religious dimensions exert a positive influence on physical and mental health as well as on general well-being, scholars have found a negative relationship between religious dimensions and both income and gender equality. Studies agree that the dominance of one religious group together with parallel ethnic and religious cleavages increases the risk of conflict, while studies on the pro-peace effects of religious factors are largely missing. Methodological challenges relate to the availability of fine-grained data, especially for non-Western countries, and the use of concepts and definitions. Most importantly, the study of religion and development requires methods that allow for causal inference.
Keywords: 300; religion; sustainable development; quantitative evidence; growth; inequality; education; conflict; health; multidimensionality